Assessment of the ecological state of green spaces of Almaty city on the example of Bostandyk district - Sadyrova, G.A.; Bazarbaeva, T.A.; Mukanova, G.A.; Jamilova, S.M. (Karagandy University of the name of acad. E.A. Buketov, 2023)
The article provides an assessment of the ecological state of green spaces on the example of the Bostandyk district of Almaty. The total area of boulevards, squares and green areas of the Bostandyk district of Almaty today is 147.4 hectares. Bostandyk district of Almaty is one of the three greenest districts of Almaty after Medeu and Turksib districts. As our studies have shown, 95 % of green plantations of tree species in the Bostandyk district of Almaty are represented by introducers and a small part of local species — natives. The landscaping of the territory of the city of Almaty is represented by plantings of different types. These include groves, alleys, gardens, parks, boulevards, squares, green areas, intra-district gardening, street gardening. At the same time, a wide variety of species is observed in gardens, parks, boulevards, groves and a very small use of three or four species in landscaping streets. Among the tree plantations, 35 species are massive, which grow along all the streets, boulevards, squares of the Bostandyk district. From hardwoods: Populus nigra, Populus italica, Populus alba, Fraxinus excelsior and others. From the local natural flora grow — Armeniaca vulgaris, Prunus sogdiana, Fraxinus sogdiana, Rhamnus cathartica, Picea schrenkiana.
Жасыл желектердің экологиялық жағдайын бағалау Алматы қаласының Бостандық ауданы мысалында
Оценка экологического состояния зеленых насаждений города Алматы на примере Бостандыкского района
Keywords: Almaty city; Bostandyk district; green spaces; urban environment; air pollution